2018
DOI: 10.1215/00031283-6926157
|View full text |Cite
|
Sign up to set email alerts
|

Vowel Dynamics in the Southern Vowel Shift

Abstract: Southern varieties of English are known to be affected by the Southern Vowel Shift (SVS), which alters the positional relationship between the front tense/ lax system. However, previous work on the SVS generally limits its focus to steady state formant measures. Possible links between these shifts and dynamic trajectory distinctions have largely been unexplored despite widespread recognition that Southern vowels are dynamic in nature. The current article uses data from three Southern states (Tennessee, North C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 41 publications
(89 reference statements)
0
20
0
Order By: Relevance
“…While we stress the importance of vowel dynamics, we acknowledge that we work under the assumption that vowel-inherent spectral change is perceptually relevant and sociolinguistically meaningful. Some work has been done to support this assumption in the Southern US (e.g., Fridland & Kendall 2012;Farrington, Kendall & Fridland 2018;Gunter, Vaughn & Kendall 2020;Jacewicz & Fox 2020), though we leave such perceptual work on DASS for the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we stress the importance of vowel dynamics, we acknowledge that we work under the assumption that vowel-inherent spectral change is perceptually relevant and sociolinguistically meaningful. Some work has been done to support this assumption in the Southern US (e.g., Fridland & Kendall 2012;Farrington, Kendall & Fridland 2018;Gunter, Vaughn & Kendall 2020;Jacewicz & Fox 2020), though we leave such perceptual work on DASS for the future.…”
Section: Discussionmentioning
confidence: 99%
“…Holt (2016) takes a different approach to analyze whether there is regional variation in formant dynamics within North Carolina. One analytic measure used was the spectral rate of change, which measures how quickly formants change and how that speed varies over the course of the duration of the vowel (Farrington, Kendall & Fridland 2018). Holt (2016) finds that European American speakers realize GOOSE and GOAT with different spectral rates of change, with speakers in western North Carolina having a lower rate of change (meaning more monophthongal vowels) than speakers in eastern North Carolina.…”
Section: The Role Of Dynamics In Back Vowelsmentioning
confidence: 99%
“… 2. Our recent and ongoing work (Farrington, Kendall, & Fridland, 2015; Fridland et al, 2014) has indicated that the low vowels are differentiated both within and among regions by durational and spectral distinctions beyond those captured by standard F1 and F2 measures. However, for sake of space, we limit our focus in this paper to measures relating to or derived from F1 and F2 measurements taken at vowel onsets. …”
Section: Notesmentioning
confidence: 97%
“…Thus, we ask: do shorter /aɪ/ glides cooccur with -in productions? In our data, glide lengths for /aɪ/ vowels were measured as the Euclidean distance between normalized F1 and F2 values at the 20% and 80% points in each /aɪ/ vowel's duration (corresponding to the Vector Length measurement of JACEWICZ, 2009 andFARRINGTON et al, 2018).…”
Section: Additional Sociolinguistic Variants Examinedmentioning
confidence: 99%